Pengaruh Institutional Ownership, Capital Intensity, Dan Ketidakpastian Lingkungan Terhadap Financial Distress (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2018–2022) - Adella Syabrinawati Putri; Ifan Wicaksana Siregar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The company needs to maintain stability and business sustainability to compete in the business world and avoid the possibility of financial distress. This research aims to identify and analyze the influence of institutional ownership, capital intensity, and environmental uncertainty on financial distress in manufacturing companies listed on the Indonesia Stock Exchange for the period 2018–2022. The population in this study consists of 225 manufacturing companies listed on the Indonesia Stock Exchange during the period 2018–2022. The sampling technique used is purposive sampling with a total sample of 140 companies and a 5-year observation period, resulting in a total of 700 samples. The data analysis technique employed is multiple linear regression analysis. The results of this study conclude that, partially, institutional ownership and environmental uncertainty do not affect financial distress, while capital intensity has a significant negative impact on financial distress. Simultaneously, institutional ownership, capital intensity, and environmental uncertainty do not affect financial distress. Keywords: Institutional Ownership, Capital Intensity, Environmental Uncertainty, Financial Distress